2022
DOI: 10.1002/ddr.21914
|View full text |Cite
|
Sign up to set email alerts
|

Verbascoside enhances radiosensitivity of hepatocellular carcinoma cells through regulating miR‐101‐3p/Wee1 axis

Abstract: Verbascoside is a kind of phenylpropanoid glycoside derived from multiple medicinal plants, exerting anti-tumor effects in diverse human malignancies. However, the function of Verbascoside on the radiosensitivity of hepatocellular carcinoma (HCC) cells remains unknown. Human Huh7 and HepG2 cell lines were treated with Verbascosideis, and cell viability was detected with cell counting kit-8 (CCK-8) assay. Quantitative real-time polymerase chain reaction (qRT-PCR) was applied to detect miR-101-3p expression, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…For example, microRNA (miRNA) induced gene repression by binding to 3′‐untranslational regions (3′UTR) of target mRNA. In HCC, a reduction in miR‐101‐3p expression has been reported, together with its association with the proliferation of liver cancer cells 13–16 . MiR‐101‐3p was a key tumor‐related gene with potential preclinical development applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, microRNA (miRNA) induced gene repression by binding to 3′‐untranslational regions (3′UTR) of target mRNA. In HCC, a reduction in miR‐101‐3p expression has been reported, together with its association with the proliferation of liver cancer cells 13–16 . MiR‐101‐3p was a key tumor‐related gene with potential preclinical development applications.…”
Section: Introductionmentioning
confidence: 99%
“…In HCC, a reduction in miR-101-3p expression has been reported, together with its association with the proliferation of liver cancer cells. [13][14][15][16] MiR-101-3p was a key tumor-related gene with potential preclinical development applications. Meanwhile, it is suggested that ARHGAP1 is a potential post-transcriptional target of cancer-related miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…In serous ovarian cancer, miR-101-3p was found to inhibit epithelial–mesenchymal transition and tumor invasion and metastasis by regulating the PTAR/ZBE1 axis [ 25 ]. miR-101-3p has also been found to be involved in HCC progression and radiosensitivity [ 26 , 27 ]. However, there is very little research about the interaction between PDZK1 and miR-101-3p in HCC.…”
Section: Introductionmentioning
confidence: 99%